Lipophillically dispersed phenolic polymer particles

By modifying phenolic polymers to be lipophilic, they can be used in oil phases of formulations, enhancing their water resistance and UV blocking capabilities, addressing solubility issues and improving their effectiveness in topical applications.

JP2025000923APending Publication Date: 2025-01-07NANOPHASE TECHNOLOGIES CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024173098
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-09-13
Filing Date
2024-10-02
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Phenolic polymers, particularly lignin, are highly water-soluble, limiting their use in topical formulations due to solubility concerns, which restricts their application in solid states and reduces their effectiveness as antioxidants and UV blockers.

Method used

Modification of phenolic polymers to make them lipophilic by adding surfactants or silanizing agents, allowing them to be incorporated into oil phases of formulations, thereby maintaining their properties in solid form.

Benefits of technology

Lipophilic phenolic polymers exhibit enhanced water resistance, ultra-photostability, and effective free radical quenching, making them suitable for sunscreen formulations and providing broad-spectrum UV and HEV radiation protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025000923000009
    Figure 2025000923000009
  • Figure 2025000923000001
    Figure 2025000923000001
  • Figure 2025000923000002
    Figure 2025000923000002
Patent Text Reader

Abstract

To provide lipophilic phenolic polymer particles.SOLUTION: A composition comprises phenolic polymer particles and a surfactant on the phenolic polymer particles. The composition is lipophilic. A dispersion comprises the phenolic polymer particles, the surfactant, and a carrier vehicle. The carrier vehicle may be a cosmetically-acceptable fluid or a wax that is lipophilic.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Background technology]

[0001] Phenolic polymers are a class of organic polymers characterized by the presence of multiple OH-substituted phenyl groups.Phenolic polymers have some unique properties, such as the ability to function as antioxidants or skin conditioning agents.These properties have led to their inclusion in topically applied formulations, such as cosmetic and dermatological preparations.Well-known examples of phenolic polymers include lignin, lignosulfonates, humates, and tannins.

[0002] Lignin is a particularly desirable phenolic polymer because of its ubiquity. Modern papermaking processes involve the removal of lignin from lignocellulose. The global paper industry generates approximately 40–50 million tons of lignin as waste annually (The International Lignin Institute, "About lignin", available online at www.ili-lignin.com / aboutlignin.php (accessed August 30,2019)). Lignin is extracted from wood pulp and then recycled to the paper industry. It is also produced as a by-product of sulfite cooking to remove lignin. Waste lignin is typically incinerated to provide energy for the paper plant that generated it. Methods have been developed to convert waste lignosulfonates and kraft lignin into useful commodities. For example, high quality lignin can be obtained from black liquor produced in the kraft process for papermaking using the LIGNOBOOST® process or the LIGNOFORCE™ process. However, tens of millions of tons of waste lignin are produced each year that could be converted into useful chemical products.

[0003] Despite their ready availability as raw materials, formulation challenges limit the demand for phenolic polymers. Lignin and other phenolic polymers are highly soluble in water. As a result, phenolic polymers are only included in the aqueous phase of formulations. The high water solubility of phenolic polymers also limits their inclusion in topical formulations in the solid state, as they will wash off the skin of the user upon exposure to water. These solubility concerns limit manufacturers' ability to fully utilize the useful properties of phenolic polymers. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] The International Lignin Institute, "About lignin", available online atwww.ili-lignin.com / aboutlignin.php (accessed August 30, 2019) Summary of the Invention [Means for solving the problem]

[0005] In a first aspect, the invention is a composition comprising phenolic polymer particles and a surfactant on said phenolic polymer particles.

[0006] In a second aspect, the invention is a dispersion comprising sodium lignosulfonate particles, a surfactant, and a carrier medium. The sodium lignosulfonate particles have a particle size of 0.1 to 1.0 microns. The dispersion is flowable.

[0007] In a third aspect, the invention is a dispersion including silanated phenolic polymer particles and a carrier medium.

[0008] In a fourth aspect, the invention is a lipophilic phenolic polymer particle.

[0009] definition The term "phenolic polymer" refers to a water-soluble polymer that contains multiple OH-substituted phenyl groups. Examples of phenolic polymers include lignins, humates, tannins, and plant extracts that contain water-soluble and / or water-dispersible components.

[0010] The term "ultraviolet radiation" refers to electromagnetic radiation having a wavelength between 10 and 400 nm. Ultraviolet radiation is also referred to as ultraviolet light, UV rays or UV light. The abbreviation "UV" is used interchangeably with the expression "ultraviolet light" in this application.

[0011] The term "high energy visible radiation" or "HEV radiation" refers to electromagnetic radiation having wavelengths between 400 and 490 nm. HEV radiation is perceived as blue and violet light in the visible spectrum.

[0012] The term "particle size" refers to particles determined by static light scattering (ISO 13320:2009 Particle Size Analysis - Laser Diffraction Methods) based on number distribution, unless otherwise stated. D50) means the median particle size.

[0013] The term "highly water-resistant" refers to the monochromatic protection factor (MPF) of a compound prior to exposure and to its MPF after an 80-minute in vitro water immersion sequence. "MPF" refers to a composition that shows a change in MPF ​​of less than 50% between measurements (Cosmetics Europe, "Guidelines for evaluating sun product water resistance", available online at www.cosmeticseurope.eu / files / 7914 / 6407 / 7400 / Guidelines_for_Evaluating_Sun_Product_Water_Resistance_-_2005.pdf, 15 pages (2005)).

[0014] The "Modified DPPH Photostability Test" is a measure of the photostability of an active substance. The Modified DPPH Photostability Test is a more sensitive test than the DPPH Photostability Test described in U.S. Patent Application Publication No. 2018 / 0291210 and has been validated for compositions other than zinc oxide. First, 0.025 g ± 0.001 g of the active substance is added to four 50 mL disposable plastic beakers. 0.0125% di(phenyl)-(2,4,6-trinitrophenyl)iminoazanium (DPPH, di(phenyl)-(2,4,6-trinitrophenyl)iminoazanium; also known as diphenylpicrylhydrazyl; CAS number 1898-66-4) ethyl acetate is added to four 50 mL disposable plastic beakers. Prepare a solution in ethylene glycol butyl ether (BCS) Add 19.975 g ± 0.001 g of a 0.0125% solution of DPPH in BCS to each beaker containing the active agent to form the test mixture. Stir the test mixture thoroughly with a glass stir rod and sonicate each test mixture for 20 seconds to ensure adequate dispersion of the active agent. After sonication, transfer each test mixture to a labeled scintillation vial. Measure the absorbance of the test mixture with a calibrated colorimeter to obtain a pre-irradiation reading. After taking the reading, the test mixture is irradiated with a Q-Labs QUV Weatherometer at 0.35 Wm -2 s -1 The mixture is exposed to UV light for 10 minutes at a constant temperature of 50° C. using a 1000-μm UVA bulb. After irradiation, the absorbance of the test mixture is measured with a colorimeter. The photostability after UV exposure is determined by the persistence of the purple color due to the dye's absorption band at 520 nm.

[0015] Photostability is the total color change (L * a * b * ΔE can be expressed as a color difference (ΔE in color space) according to the definition of the International Commission on Illumination Standard CIE76, as shown in the following formula 1:

[0016]

number

[0017] [In the formula, L * 2, a * 2 and b * 2 is the color coordinate of the test mixture after irradiation, and L * 1, a * 1st place B * 1 are the color coordinates of the test mixture before irradiation] Data are reported as the average ΔE value of four samples.

[0018] The term "ultra-photostable" means a material that has a ΔE≦4.5 when subjected to a modified DPPH photostability test.

[0019] The "Free Radical Quenching Test" is a measure of the ability of an active substance to quench free radicals. First, the photostability of titanium dioxide (35 nm, rutile phase) was measured according to a modified DPPH photostability test to obtain a reference photostability (ΔE 参照 A test mixture is then prepared containing the same weight percent of titanium dioxide and an equivalent amount of active material as used to determine the reference photostability. The photostability of the test mixture is then measured according to a modified DPPH photostability test to determine the test photostability (ΔE 試験 ) is then determined. 参照 ) and test light stability (ΔE 試験 The free radical quenching ability of the active is determined by calculating the percentage difference between the free radical quenching ability of the active and the free radical quenching ability of the active. The active quenches at least 70% of the free radicals generated by titanium dioxide (ΔE 試験 is ΔE 参照 If the α-to-α bond is at least 70% smaller than the α-to-α bond, the free radical quenching test is passed.

[0020] Unless otherwise stated, all percentages (%) are weight / weight percentages.

[0021] The invention can be better understood with reference to the following drawings and description. [Brief description of the drawings]

[0022] [Figure 1] FIG. 2 is a schematic diagram showing a phenolic polymer particle modified with a surfactant. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present invention includes phenolic polymer particles that are modified to be lipophilic. Lipophilic phenolic polymer particles can be formed by adding a surface treatment agent to the particles or by reacting the particles with a silanizing agent. Lipophilic modification allows the phenolic polymer to exist in a solid state in the oil phase of the formulation. For example, the phenolic polymer particles and surfactants can be dispersed in a lipophilic carrier medium. The ability to use phenolic polymer particles in the oil phase greatly expands the possible applications of these particles.

[0024] Experiments have revealed that formulations containing lipophilic phenolic polymer particles have several desirable physical and chemical properties. These formulations are highly water resistant and are strong HEV light blocking agents, indicating that they are well suited for use in sunscreen formulations. The formulations are also ultra-photostable when subjected to a modified DPPH photostability test. In addition, the formulations pass the free radical quenching test, indicating their strong antioxidant capabilities.

[0025] Without wishing to be bound by any theory, it is believed that these properties are due to the existence of the phenolic polymer in the solid state. The interfacial interactions result in pi (π) stacking of the aromatic groups, which improves the ability of these molecules to accept electrons through orbital mixing. Pi stacking can occur when the phenolic polymers are in solution, but the solution must have a sufficiently high concentration. Delivering the phenolic polymers as particles (i.e., in the solid state) ensures that they have pi stacking.

[0026] Formulations containing phenolic polymer particles also offer several commercial advantages. Phenolic polymers, especially lignin, are available in significant quantities as waste materials, making them an economically advantageous raw material. Obtaining waste materials that would otherwise be burned is an environmentally friendly method, as it prevents carbon emissions. Phenolic polymers derived from natural sources may be sold as natural products, which are particularly attractive to consumers. Furthermore, dispersions of phenolic polymer particles can be produced using conventional chemical processing techniques that do not require expensive reactants, extreme temperatures, long reaction times, or dangerous reactants, and do not produce hazardous waste products. All these advantages will encourage manufacturers to include phenolic polymers in commercial formulations.

[0027] FIG. 1 shows a schematic diagram of surfactant-modified phenolic polymer particles. Composition 100 includes phenolic polymer particles 110 and a surfactant 120 on the surface of the particles. The surfactant is a surface treatment that makes the phenolic polymer particles lipophilic and resistant to dissolution in water. A dispersion may be prepared by combining the phenolic polymer particles, the surfactant, and a carrier medium. Preferably, the dispersion is flowable.

[0028] The phenolic polymer particles may be any polymer having multiple OH-substituted phenyl groups. Preferably, the phenolic polymer particles are lignins, humates, tannins, plant extracts containing water-soluble and / or water-dispersible components, or combinations thereof. Examples of suitable lignins include lignosulfonates; kraft lignin; sulfonated kraft lignin; oxylignin; sulfonated oxylignin; lignosulfonates copolymerized with monomers such as acrylates, acrylic acid, acrylamide, styrene sulfonate, and naphthalene sulfonate derivatives; azolignosulfonates; azolignins; lignosulfonate-formaldehyde condensates; lignin formaldehyde condensates; hydrophobically modified lignosulfonates; hydrophobically modified lignins; cationically modified lignosulfonates; cationically modified lignins; aminolignosulfonates; aminolignins; alkylated lignosulfonates; alkylated lignins; crosslinked lignosulfonates; and crosslinked lignins. Suitable humates include sulfonated humates, humate-formaldehyde condensates, hydrophobically modified humates, cationically modified humates, aminohumates, and alkylated humates. Examples of suitable tannins include tannates, sulfonated tannates, tannate-formaldehyde condensates, hydrophobically modified tannates, and cationically modified tannates.

[0029] Examples of plant extracts containing water-soluble and / or water-dispersible components include those from the genus Acacia, Afzelia, Synsepalum duloificum, Albizia, alder (e.g., Alnus glutinosa and Alnus rubra), applewood, Arbutus, ash (e.g., F. nigra, F. quadrangulata, F. excelsior, F. pennsylvanica lanceolata, F. latifolia, pumpkin, and the like. Ash (F. profinda) and American ash (F. americana), poplars (e.g., P. grandidentata, P. tremula, P. tremuloides), Australian Anchanchin (Toona ciliata), Ayang (Distemonanthus benthamianus), Balsa (Ochromapyramidale), Basswood (e.g., T. americana and T. heterophylla), Beech (e.g., F. sylvatica and F. grandifolia), Birch (e.g., Betula populifolia), River birch (B. nigra), White birch (B. papyrifera), American water hyacinth (B. lenta), Yellow birch (B. -birch (B. alleghaniensis / B. lutea), Finland birch (B. pendula) and European birch (B. Betula pubescens, Black Bean, Blackwood, Bocote, Bok Horse chestnut, boxwood, brazilwood, bubinga, horse chestnut (e.g. Aesculus hippocastianum, Aesculus glabra and Aesculus flava / Aesculus octandra), butternut, catalpa, cherry (e.g. Prunus serotina, Prunus pennsylvanica and Prunus avium), crabwood, chestnut, coachwood, Cocobolo, corkwood, cottonwood (e.g., Populus balsamifera, Populus deltoides, Populus sargentii, and Populus heterophylla), bilimbi, dogwood ( For example, Cornus florida and Cornus nuttallii), Ebony (Diospyros kurzii, Diospyros melanida and African ebony (Diospyros crassiflora), (e.g., American elm (Ulmus americana), European elm (Ulmus procera), rock elm (Ulmus thomasii), Ulmus rubra and Ulmus glabra), eucalyptus, greenheart, grenadilla, gums (e.g., Nyssa Nyssa sylvatica, Eucalyptus globulus, Liquidambar styraciflua and Nyssa aquatica, Hickory (e.g., Carya alba, Carya glabra, Carya ovata, and Carya laciniosa), hornbeam, hop hornbeam, ipe, iroko, ironwood (e.g., Bangkirai, American hornbeam, Casuarina equisetifolia, Choricbangarpia subargentea, copaifu), Copaifera spp., Eusideroxylon zwageri, Copaifera spp. Guaiacum officinale, Guaiacum sanctum, Takia Hopea odorata, Black Ironwood (Krugiodendron ferreum), Lionothamnus ivonii (Cathalina Ironwood (L. floribundus) ), Mesua ferrea, Olea spp., Olean teso Olneya tesota, Ostrya virginiana, Parrotia persica and Tabebuia serratifolia, Caranda, Jojoba, Lacewood, Bay, Limba, Lignum vitae, Black Locust (e.g. Robinia pseudacacia) and Honeyrow Gleditsia triacanthos), mahogany, maples (e.g., Acer saccharum, Acer nigrum, Acer negundo, Acer rubrum, Acer saccharinum, and seitan maple). Acer pseudoplatanus, Meranti, American Blackwood, oaks (e.g., bur oak (Quercus macrocarpa), American white oak (Quercus alba), bost oak (Quercus stellata), swamp white oak (Quercus bicolor), southern live oak (Quercus virginiana), swamp chestnut oak (Quercus michauxii), chestnut oak (Quercus prinus), chinkapin oak (Quercus muhlenbergii), canyon live oak (Quercus chrysolepis), overcast Overcup oak (Quercus lyrata), European oak (Quercus robur), Cecil oak (Quercus petraea), American oak (Quercus rubra), Black oak (Quercus velutina), Overcup oak (Quercus laurifolia), Spanish red oak (Quercus oak (Quercus falcata), water oak (Quercus nigra), willow oak (Quercus phellos) and Quercus texana), obeche, okoume, Oregon myrtle, California bay laurel, European pear, poplar (e.g., balsam poplar (P. balsamifera), European aspen (P. nigra) and hybrid poplar (Populus canadensis)), ramin, red cedar, rosewood, sal, sandalwood, sassafras, Indian oak, Chinese oak, Japanese silverleaf, sourwood, Spanish cedar, plane tree, teak, walnut (e.g., black walnut (Juglans nigra) and walnut (Juglans regia)), willow (e.g., Salix nigra), nigra) and White Willow (Salix alba) Low poplar (Liriodendron tulipifera), Araucaria (e.g., hoop pine (A. cunninghamii), parana pine (A. angustifolia) and Chilean pine (A. angustifolia). pine (A. araucana), coniferous cedars (e.g., Juniperus virginiana, Thuja plicata, Thuja occidentalis, Atlantic white cedar (Chamaecyparis thyoides and Callitropsis nootkatensis), cypresses (e.g., Chamaecyparis, Cupressus taxodium, Cupressus arizonica, Bald cypress (Taxodium distichum), Chamaecyparis obtusa), Lawson cypress (Chamaecyparis lawsoniana) and Cupressus semperviren, Rocky Mountain Douglas fir, European yew, fir (e.g., Abies balsamea, Abies alba, Abies procera, and Abies amabilis), western hemlock (e.g., Tsuga canadensis, Mountain hemlock, Tsuga mertensiana and Tsuga heterophylla), Kauri, Kaya, Kaya larch (e.g. Larix decidua, Larix kaempferi, Larix laricina, Larix occidentalis and Larix europea), pines (e.g. Pinus nigra, Pinus banksiana, Pinus contorta, Rajasthan), Pinus radiata, Ponderosa pine, Red pine, Scots pine, White pine, Monticola pine, Sugar pine, Included are extracts derived from plants known as loblolly pine (Pinus taeda, Pinus palustris, Pinus rigida, and Pinus echinata), redwood, ream, spruce (e.g., Picea abies, Picea mariana, Picea rubens, Picea sitchensis, and Picea glauca), cedar, and mixtures / hybrids thereof. Preferred plant extracts containing water-soluble and / or water-dispersible components include extracts derived from Norway spruce (also known as Norway spruce and European spruce), European larch (also known as larch or European larch), and mixtures of the maple species Acer platyphylla, Acer platyphylla, and Acer arborescens.

[0030] The surfactant may be any surfactant that has a strong acid-base interaction with the phenolic polymer particles and provides a lipophilic surface treatment on the particles. Examples of suitable surfactants include fatty alcohols and polyols (e.g., stearyl alcohol, behenyl alcohol and cetearyl alcohol), fatty acids (e.g., stearic acid and oleic acid), amino acids (e.g., lauroyl lysine and myristoyl glutamate), polyglyceryl esters (e.g., polyglyceryl-3 ricinoleate, polyglyceryl-6 ricinoleate, polyglyceryl-10 pentastearate and polyglyceryl-4 oleate), polyglyceryl polyesters (e.g., polyglyceryl-4 (diisostearate / polyhydroxystearic acid / sebacic acid), polyglyceryl-2 polyhydroxystearate, polyglyceryl-10 dipolyhydroxystearate, polyglyceryl-10 diisostearate, polyglyceryl-2 polyhydroxystearate, polyglyceryl-10 diiso ... 2 and polyglyceryl-3 stearate / isostearate / dimer dilinoleate crosspolymers), polyesters having affinity hydroxyl, amine or amide groups (e.g., polyhydroxystearic acid), polyurethanes having affinity hydroxyl, amine or amide groups, polyamides having affinity hydroxyl, amine or amide groups, polyacrylates having affinity hydroxyl, amine or amide groups, phosphate esters (e.g., trilaureth-4 phosphate and triceteareth-4 phosphate), polymeric phosphates (e.g., 1,2-ethanediamine, polymers containing aziridine, compounds containing N-[3-[(2-ethylhexyl)oxy]-3-oxypropyl] derivatives and polyethylene-polypropylene glycol), phospholipids, ceramides, sphingosides (e.g., lecithin, oleic acid ... cytin, lysolecithin and ceramide 3), substituted silicones having affinity groups (e.g., cetyl diglyceryl tris(trimethylsiloxy)silylethyl dimethicone, CAS number 104780-66-7 (siloxane and silicone, di-Me, 3-hydroxypropyl terminated), CAS number 102782-61-6 (siloxane and silicone, di-Me, 3-hydroxypropyl Me), and CAS number 106214-84-0 (siloxane and silicone, dimethyl, 3-aminopropyl)), and combinations thereof.

[0031] Alternatively, lipophilic phenolic polymer particles may be formed by reacting the particles with a silanizing agent. The silanizing agent may be any material that provides functionalized polysiloxane on the surface of the phenolic polymer particles. Examples of suitable silanizing agents include reactive silicone and silane hydrophobic surface treatment agents (e.g., triethoxycaprylylsilane, octadecyltriethoxysilane, hydrogen dimethicone (CAS No. 68037-59-2 / 69013-23-6 / 70900-21-9) and CAS No. 69430-47-3 (siloxane and silicone, reaction product of di-Me, Me hydrogen siloxane and 1,1,3,3-tetramethyldisiloxane)).

[0032] The carrier medium may be any cosmetically acceptable fluid or wax that is lipophilic. Examples of suitable carrier media include triglycerides (e.g., caprylic / capric triglycerides), esters (e.g., benzoic acid, Alkyl (C12-C15), isopentyl laurate, isopropyl isostearate, coco-caprylate, ethylhexyl isononanoate, tridecyl salicylate, ethylhexyl isononanoate, isodecyl salicylate, octyldodecyl neopentanoate, butyloctyl salicylate, jojoba esters and shea butter esters), natural oils and butters (e.g., Simmondsia chinensis (jojoba) seed oil, shea butter, Argania spinosa (argan) oil, pongami (karanja) oil and Limnanthes alba (meadowfoam) seed oil). oils), alkanes (e.g., squalane, hemisqualane, isododecane, and isohexadecane), silicones (e.g., dimethicone, behenyl dimethicone, cetyl dimethicone, cetearyl methicone, and phenyl dimethicone), waxes (e.g., natural waxes, synthetic waxes, and silicone waxes), and combinations thereof.

[0033] The phenolic polymer particles may be present in the dispersion in an amount of 0.1 to 75.0% by weight, including 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 15.0%, 20.0%, 25.0%, 30.0%, 35.0%, 40.0%, 45.0%, 50.0%, 55.0%, 60.0%, 65.0% and 70.0% by weight. Preferably, the phenolic polymer particles are present in an amount of 0.5 to 50.0% by weight. More preferably, the phenolic polymer particles are present in an amount of 1.0 to 40.0% by weight.

[0034] The surfactants accounted for 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, and 10.0% of the mass of the phenolic polymer particles. The surfactant may be present in the dispersion in an amount of 1.0 to 100.0% of the mass of the phenolic polymer particles, including 0%, 15.0%, 20.0%, 25.0%, 30.0%, 35.0%, 40.0%, 45.0%, 50.0%, 55.0%, 60.0%, 65.0%, 70.0%, 75.0%, 80.0%, 85.0%, 90.0% and 95.0%. Preferably, the surfactant is present in an amount of 10.0 to 60.0% of the mass of the phenolic polymer particles. More preferably, the surfactant is present in an amount of 20.0 to 50.0% of the mass of the phenolic polymer particles.

[0035] The amount of carrier medium in the dispersion depends on the amount of phenolic polymer particles and the amount of surfactant present in the dispersion. After combining the phenolic polymer particles and the surfactant, the carrier medium can be added in any suitable amount necessary to produce the desired dispersion.

[0036] The dispersion may be prepared by conventional compounding techniques. For example, the phenolic polymer particles, surfactant and carrier medium may be combined in a vessel and stirred until homogeneous. Appropriate mixing conditions, such as temperature, stirring speed and mixing time, may be altered to provide the desired dispersion. The dispersion may then be transferred to a mill, such as a media mill, and milled to achieve the desired particle size.

[0037] Phenolic polymer particles are available in sizes 0.002 microns (μm), 0.003 μm, 0.004 μm, 0.005 μm, 0.006 μm, 0.007 μm, 0.008 μm, 0.009 μm, 0.01 μm, 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0. The phenolic polymer may have a particle size of 0.001 to 10.0 μm (1 to 10,000 nm), including 9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm and 9.5 μm. Preferably, the phenolic polymer has a particle size of 0.01 to 5.0 μm (10 to 5,000 nm). More preferably, the phenolic polymer has a particle size of 0.1 to 1.0 μm (100 to 1,000 nm). In order to prevent the perception of the particles on the skin and to avoid the formulation having a gritty or rough texture to the user, the maximum particle size of the phenolic polymer particles is 10.0 μm.

[0038] The lipophilic phenolic polymer particles may be obtained by removing the carrier medium from the dispersion of the phenolic polymer particles, the surfactant and the carrier medium. For example, the carrier medium may be a volatile material that evaporates at ambient temperature and pressure. Similarly, the dispersion may be heated above the boiling point of the carrier medium until the carrier medium is removed.

[0039] The lipophilic phenolic polymer particles may also be prepared directly, rather than by isolation from a dispersion. First, the particle size of the phenolic polymer particles is reduced by dry milling. Any suitable dry milling technique may be used, such as high performance air milling, vibratory milling, media milling, hammer milling and jet milling. Milling may be performed neat or in combination with secondary materials, such as polymer particles or oxides (e.g., metal oxides and silicates, such as mica or silica). Next, a solution is prepared by dissolving the surfactant or silanizing agent in a suitable solvent. Examples of suitable solvents include USP heptane, USP acetone, USP isopropanol and USP ethanol. The solution is then blended with a blender. The solution is sprayed onto the finely divided phenolic polymer particles while stirring in a pusher / mixer. The solution and finely divided phenolic polymer particles may optionally be heated to drive a reaction to bond the surfactant or silanizing agent to the particles. Finally, a vacuum is applied to remove the solvent.

[0040] The lipophilic phenolic polymer particles may be present in the oil phase of the formulation or may be added to a powder formulation. Preferably, the formulation is suitable for topical application. Examples of suitable formulations include emulsions (oil-in-water and water-in-oil emulsions), sprays, balms, sticks, powders, powder-cream formulations, lipophilic formulations and anhydrous formulations. The formulations containing lipophilic phenolic polymer particles may be evaluated by one or more tests. Preferably, the formulations containing lipophilic phenolic polymer particles are highly water-resistant, ultra-photostable and pass the free radical quenching test.

[0041] The preparation containing the lipophilic phenolic polymer particles can be formulated for use in a variety of different applications. Examples of suitable formulations include cosmetics (e.g., blush, face powder, foundation, lipstick, makeup base and blush), skin care products (e.g., skin cleansing creams, lotions, liquids and pads; face and neck creams, lotions, powders and sprays; body and hand creams, lotions, powders and sprays; foot powders and sprays; moisturizers; night creams, lotions, powders and sprays; paste masks / mud masks; and skin fresheners), and sunscreens. Sunscreens are particularly preferred formulations. The formulations may be provided in any form suitable for topical administration, for example, in the form of topical suspensions, lotions, creams, ointments, gels, hydrogels, foams, pastes, tinctures, liniments, sprayable liquids, aerosols, sticks or powders. The formulation may optionally contain inactive ingredients, auxiliaries and / or additives such as co-emulsifiers, fats, waxes, stabilizers, thickeners, active ingredients of biological origin, film formers, fragrances, dyes, pearlescent agents, preservatives, pigments, electrolytes and pH adjusters.

[0042] The sunscreen may comprise lipophilic phenolic polymer particles and a UV protection agent. The UV protection agent may be any material that absorbs, reflects and / or scatters UV radiation. The sunscreen may optionally contain a sun protection factor booster or stabilizer, For example, they may include methoxycrylene and polyester-8.

[0043] Examples of suitable UV protection agents include zinc oxide (ZnO), titanium dioxide (TiO2), p-aminobenzoic acid (PABA), padimate O (OD-PABA, octyldimethyl-PABA, σ-PABA), phenylbenzimidazole sulfonic acid (ensulizole, EUSOLEX® 232, PBSA, PARSOL® HS), cinoxate (2-ethoxyethyl p-methoxycinnamate), dioxybenzone (benzophenone-8), oxybenzone (benzophenone-3, EUSOLEX® 4360, ESCALOL® 567), homosalate (homomethyl salicylate, HMS), menthyl anthranilate (merazimate), octocrylene (EUSOLEX® OCR, 2-cyano-3,3-dibenzoyl) Phenylacrylic acid, 2-ethylhexyl ester), Octyl Methoxycinnamate (Octinoxate, EMC, OMC, Ethylhexyl Methoxycinnamate, ESCALOL® 557, 2-Ethylhexyl-paramethoxycinnamate, PARSOL® MCX), Octyl Salicylate (Octisalate, 2-Ethylhexyl Salicylate, ESCALOL® 587), Sulisobenzone (2-Hydroxy-4-Methoxybenzophenone-5-Sulfonic Acid, 3-Benzoyl-4-Hydroxy-6-Methoxybenzenesulfonic Acid, Benzophenone-4, ESCALOL® 577), Trolamine Salicylate (Triethanolamine Salicylate), Avobenzone (1-(4-Methoxyphenyl)-3-(4-tert-butyl phenyl)propane-1,3-dione, butyl methoxydibenzoylmethane, BMDBM, PARSOL® 1789, EUSOLEX® 9020), ecamsul (MEXORYL® SX, terephthalylidene dicamphor sulfonic acid), cerium oxide (CeO2), drometrizole trisiloxane (MEXORYL® XL), bisethylhexyloxyphenol methoxyphenyl triazine (TINOSORB® S), bisoxotrizole (TINOSORB® M, MILESTAB™ 360), and combinations thereof. Preferred UV radiation protection agents include zinc oxide (ZnO), titanium dioxide (TiO2), and combinations thereof. Preferably, the UV protection agent is approved by at least one of the regulatory agencies of the United States (Food and Drug Administration or FDA), Canada, the European Union, Australia, Japan, South Korea, China, Mercosur, the Association of Southeast Asian Nations (ASEAN), the Commonwealth of Independent States (CIS), and the Gulf Cooperation Council (GCC).

[0044] Sunscreens containing lipophilic phenolic polymer particles offer several advantages over conventional sunscreens. The inclusion of phenolic polymer particles produces a very water-resistant sunscreen. In addition, the phenolic polymer particles enable the sunscreen to block or attenuate both UV and HEV radiation. The phenolic polymer particles are also resistant to photoinduced free radical generation by UV and HEV radiation.

[0045] Formulations containing lipophilic phenolic polymer particles provide various health benefits. Phenolic polymer particles are extremely efficient in neutralizing free radicals, so they act as antioxidants. Due to these properties, phenolic polymer particles can treat or prevent oxidative stress or damage to skin, hair and nails. For example, phenolic polymer particles can be used to protect keratinous materials (e.g., hair, fingernails, toenails and the outer layer of skin), protect human skin, inhibit lipid peroxidation, prevent or reduce wrinkles and wrinkles on the skin, prevent loss of skin elasticity, prevent skin thinning, and prevent skin pigment darkening. These health benefits can be obtained by applying a formulation containing lipophilic phenolic polymer particles to an area of ​​skin.

[0046] [Example] [Example 1] Dispersions of sodium lignosulfonate and polyglyceryl-2 dipolyhydroxystearate in tri(caprylic / capric)glyceryl 30.0 parts by weight of sodium lignosulfonate (Vanisperse A, Borregaard LignoTech) was combined with 10.5 parts by weight of polyglyceryl-2 dipolyhydroxystearate and 59.5 parts by weight of caprylic / capric triglyceride. The mixture was stirred until homogeneous, transferred to a horizontal media mill and milled using 0.3 mm yttria stabilized zirconia media until the maximum particle size was less than 0.5 microns as indicated by a Hegman gauge indicating 0 to 12 microns with a scale gradation of 0.5. The resulting dispersion was free-flowing. The particle size of the sodium lignosulfonate particles in the dispersion was measured by static light scattering to be 0.169 microns, with no particles less than 0.1 microns detected.

[0047] [Example 2] Dispersions of sodium lignosulfonate and polyglyceryl-2 dipolyhydroxystearate in coco-octyl caprylate. 30.0 parts by weight of sodium lignosulfonate (Vanisperse A, Borregaard LignoTech) was combined with 13.5 parts by weight of polyglyceryl-2 dipolyhydroxystearate and 56.5 parts by weight of coco-caprylate. The mixture was stirred until homogeneous and then mixed in a horizontal mixer. The mixture was transferred to a media mill and milled using 0.3 mm yttria stabilized zirconia media until the maximum particle size was less than 0.5 microns as indicated by a Hegman gauge indicating 0 to 12 microns with a scale gradation of 0.5. The resulting dispersion was free-flowing.

[0048] [Example 3] Dispersions of sodium lignosulfonate and polyhydroxystearic acid in coco-octanoate. 30.0 parts by weight of sodium lignosulfonate (Vanisperse A, Borregaard LignoTech) was combined with 12.0 parts by weight of polyhydroxystearic acid and 58.0 parts by weight of coco-alkyl caprylate. The mixture was stirred until homogeneous, transferred to a horizontal media mill, and milled using 0.3 mm yttria stabilized zirconia media until the maximum particle size was less than 0.5 microns as indicated by a Hegman gauge indicating 0 to 12 microns with a scale gradation of 0.5. The resulting dispersion was free-flowing.

[0049] [Example 4] Dispersions of sodium lignosulfonate and lecithin in caprylic / capric triglyceride. 30.0 parts by weight of sodium lignosulfonate (Vanisperse A, Borregaard LignoTech) was combined with 14.0 parts by weight of lecithin and 56.0 parts by weight of caprylic / capric triglyceride. The mixture was stirred until homogeneous, transferred to a horizontal media mill and milled using 0.3 mm yttria stabilized zirconia media until the maximum particle size was less than 0.5 microns as indicated by a Hegman gauge indicating 0 to 12 microns with a scale gradation of 0.5. The resulting dispersion was free flowing.

[0050] [Example 5] Dispersion of sodium lignosulfonate and polyglyceryl-2 dipolyhydroxystearate in alkyl benzoate (C12-C15) 30.0 parts by weight of sodium lignosulfonate (Maracell XE, Borregaard LignoTech (Corporation of 1,2-dihydroxystearate) was combined with 13.5 parts by weight of Polyglyceryl-2 Dipolyhydroxystearate and 56.5 parts by weight of Alkyl Benzoate (C12-C15). The mixture was stirred until homogeneous, transferred to a horizontal media mill and milled using 0.3 mm yttria stabilized zirconia media until the maximum particle size was less than 0.5 microns as indicated by a Hegman gauge indicating 0 to 12 microns with a scale gradation of 0.5. The resulting dispersion was free flowing.

[0051] [Example 6] A 2:1 mixture of sodium lignosulfonate:calcium lignosulfonate and dispersion of polyglyceryl-2 dipolyhydroxystearate in tri(caprylic / capric)glyceryl. 30.0 parts by weight of a mixture of sodium lignosulfonate:calcium lignosulfonate approximately 2:1 (Marasperse C-21, Borregaard LignoTech) was mixed with 13.5 parts by weight of dipoly Polyglyceryl-2 hydroxystearate and 56.5 parts by weight of caprylic / capric triglyceride were combined. The mixture was stirred until homogeneous, transferred to a horizontal media mill and milled using 0.3 mm yttria stabilized zirconia media until the maximum particle size was less than 0.5 microns as indicated by a Hegman gauge indicating 0 to 12 microns with a scale gradation of 0.5. The resulting dispersion was free flowing.

[0052] [Example 7] Potassium Humate and Polyglyceryl-2 Dipolyhydroxystearate Tri(caprylate) Dispersion in glyceryl caprate 30.0 parts by weight of potassium humate (Borregro HA-2, Borregaard LignoTech) Combined with 3.5 parts by weight of polyglyceryl-2 dipolyhydroxystearate and 56.5 parts by weight of caprylic / capric triglyceride. The mixture was stirred until homogeneous, transferred to a horizontal media mill and milled using 0.3 mm yttria stabilized zirconia media until the maximum particle size was less than 0.5 microns as indicated by a Hegman gauge indicating 0 to 12 microns with a scale gradation of 0.5. The resulting dispersion was free flowing.

[0053] [Example 8] Dispersion of sodium lignosulfonate and cetyl diglyceryl tris(trimethylsiloxy)silylethyl dimethicone in caprylic / capric triglyceride 30.0 parts by weight of sodium lignosulfonate (Vanisperse A, Borregaard LignoTech) was combined with 13.5 parts by weight of cetyl diglyceryl tris(trimethylsiloxy)silylethyl dimethicone and 56.5 parts by weight of caprylic / capric triglyceride. The mixture was stirred until homogeneous, transferred to a horizontal media mill, and milled using 0.3 mm yttria stabilized zirconia media until the maximum particle size was less than 0.5 microns as indicated by a Hegman gauge indicating 0 to 12 microns with a scale gradation of 0.5. The resulting dispersion was free-flowing.

[0054] [Example 9] (Comparative Example) Aqueous Slurry of Sodium Lignosulfonate and Alumina An aqueous solution of sodium lignosulfonate was prepared as described in US Patent No. 6,500,411, US Patent No. 6,716,418 and US Patent Publication No. 2010 / 0202985. Thirty parts by weight of sodium lignosulfonate (Vanisperse A, Borregaard LignoTech) were added to 70 parts by weight of deionized water. The solution was stirred until the sodium lignosulfonate was completely dissolved. To this solution, 60 parts by weight of submicron (volume D50 of 0.42 microns as measured by static light scattering) platelet alumina (E390, Saint-Gobain) were added. The resulting slurry was mixed for 30 minutes using a disperser blade. The resulting aqueous slurry was homogenous and easily flowable.

[0055] [Example 10] Moisturizers containing phenolic polymers in the oil phase A moisturizer composition was prepared as a water-in-oil emulsion containing in the oil phase the dispersion of Example 1. The components of the moisturizer composition are shown below.

[0056] [Table 1]

[0057] Using a cold process, the oil phase ingredients were combined and mixed until homogenous, and separately, the water phase ingredients were combined and mixed until homogenous. The two phases were then combined and homogenized using a Ross HSM-100LC1 homogenizer at 5,000 RPM for 4 minutes. The resulting emulsion was The emulsion was stable and very water resistant after aging for 75 days at 50° C. The presence of lipophilically dispersed phenolic polymer particles in the oil phase produced a moisturizer with HEV blocking and antioxidant properties.

[0058] [Example 11] Moisturizing sunscreen containing phenolic polymer in the oil phase A sunscreen composition was prepared as a water-in-oil emulsion containing in the oil phase the dispersion of Example 1. The components of the sunscreen composition are shown below.

[0059] [Table 2]

[0060] Using a cold process, the oil phase ingredients were combined and mixed until homogenous, and separately, the water phase ingredients were combined and mixed until homogenous. The two phases were then combined and homogenized using a Ross HSM-100LC1 homogenizer at 5,000 RPM for 4 minutes. The resulting emulsion was The emulsion was stable and very water resistant after aging for 75 days at 50° C. The presence of oleophilically dispersed phenolic polymer particles produced a moisturizing sunscreen with HEV blocking and antioxidant properties.

[0061] [Example 12] Concealer stick containing a phenolic polymer in the oil phase (unsupported example) A concealer stick composition is prepared as an anhydrous composition containing the dispersion of Example 1. The ingredients of the concealer stick are given below.

[0062] [Table 3]

[0063] Phase A is combined and mixed under high shear conditions. Phase B is added to Phase A and the mixture is heated to 85° C. under high shear conditions. Phase C is dispersed into the mixture while maintaining the temperature at 85° C. under high shear conditions. The batch is then cooled under high shear conditions. Once the mixture has cooled to below 65° C., Phases D and E are added to the mixture in stages under high shear conditions. The batch is allowed to continue to cool until the temperature reaches 60° C. The batch is then dispensed into the final package. The presence of lipophilically dispersed phenolic polymer particles produces a concealer stick with HEV blocking and antioxidant properties.

[0064] [Example 13] HEV Blocking Research The HEV blocking of the dispersion of Example 1 and the comparative aqueous slurry of Example 9 were compared. HEV blocking was measured using a diffuse transmission method similar to that described in 21 CFR § 201.327 (Over-the-counter sunscreen drug products; required labeling based on effectiveness testing) and ISO 24443 (Determination of sunscreen UVA photoprotection in vitro). Measured.

[0065] 1.3 mg / cm 2 The dispersion of Example 1 was applied to the surface of an optical grade polymethylmethacrylate (PMMA) substrate (LabSphere HelioPlate HD6) having a roughened three-dimensional surface topography. The dispersion was 0.39 mg / cm 2 The aqueous slurry of Example 9 was similarly applied to the surface of the substrate to a delivery dose of 0.39 mg / cm2 of the phenolic polymer. 2 The solution was applied evenly to the substrate to correspond to a delivered dose of phenolic polymer.

[0066] Upon visual inspection, both samples exhibited the characteristic brown color associated with light absorption in the HEV region. The samples were then left at room temperature for 1 hour. The absorbance of both samples and a control blank optical grade PMMA substrate was measured at a HEV wavelength of 450 nm using a LabSphere UV-2000S spectrophotometer. Net absorbance values ​​were determined by subtracting the absorbance of the control blank substrate from the measured absorbance of the sample on the substrate.

[0067] The monochromatic protection factor (MPF) at 450 nm was determined according to the procedure in (Bleasel, MD et al., "In vitro evaluation of sun protection factors of sunscreen agents using a novel UV spectrophotometric technique", International Journal of Cosmetic Science, Vol. 30, Issue 4, pp. 259-270 (2008)). The MPF is calculated using the following formula 2:

[0068]

number

[0069] where A(λ) is the net absorbance of the sample at wavelength λ. It can be expressed as:

[0070] The results are shown in the table below.

[0071] [Table 4]

[0072] The dispersion of Example 1 showed a higher net absorbance and a higher MPF than the aqueous slurry of Example 9. These results indicate that the phenolic polymer dispersed in the oil phase has superior HEV blocking compared to the aqueous slurry of the phenolic polymer.

[0073] [Example 14] Water resistance research The water resistance of the dispersion of Example 1 and the comparative aqueous slurry of Example 9 were compared. The water resistance was 8.0-8.0%, in accordance with COLIPA 2005 (Cosmetics Europe, "Guidelines for evaluating sun product water resistance", available online at www.cosmeticseurope.eu / files / 7914 / 6407 / 7400 / Guidelines_for_Evaluating_Sun_Product_Water_Resistance_-_2005.pdf, 15 pages (2005)). Measurements were performed using a 0 min water immersion sequence but in vitro.

[0074] A stainless steel container 22 cm high by 16 cm in diameter was filled with deionized water and maintained at a temperature of 30-33°C. The container was agitated at 350 RPM using a 5 cm diameter flat blade impeller throughout the test period. Samples of the dispersion of Example 1 and the comparative aqueous slurry of Example 9 were suspended in the container near the container wall with the applied sample facing the impeller. After 80 minutes of immersion the samples were removed from the container and allowed to dry for 1 hour. Net absorbance and monochromatic protection factor (MPF) were measured as described in Example 13. The results are shown in the table below.

[0075] [Table 5]

[0076] The dispersion of Example 1 was able to maintain 95% of its net absorbance (450 nm) and 88% of its initial MPF (450 nm) value. These results indicate that the dispersion of Example 1 is very water resistant. Visual inspection revealed that the aqueous slurry of Example 9 lost most of the characteristic brown color associated with HEV attenuation 120 seconds into the water immersion sequence. In addition, the aqueous slurry of Example 9 did not meet the requirements to be classified as very water resistant. These results indicate that the oleophilically dispersed phenolic polymer particles in the oil phase have superior water resistance compared to aqueous slurries of phenolic polymers.

[0077] [Example 15] Free radical quenching and photostability studies The dispersion of Example 1 was investigated for free radical quenching and light stability. Light stability was determined according to the modified DPPH light stability test (see definitions section). Free radical quenching was determined according to the free radical quenching test (see definitions section). Titanium dioxide was used as a comparison material since it is known to be substantially non-photostable (photocatalytic) and to generate large amounts of photoinduced free radicals upon exposure to UV radiation.

[0078] Five photostability tests were performed using various amounts of the dispersion of Example 1 and the reference titanium dioxide, and the results are shown in the table below.

[0079] [Table 6]

[0080] The results of Test 1 show that the dispersion of Example 1 is ultra-photostable. In comparison, an equivalent amount of the reference titanium dioxide (Test 4) was not ultra-photostable and generated 29 times the concentration of free radicals. Compositions containing equal amounts of the dispersion of Example 1 and titanium dioxide (Tests 2 and 3) were ultra-photostable. This indicates that the dispersion of Example 1 actively quenches 73.7% to 94.7% of the free radicals generated by the highly photoactive reference material. The dispersion of Example 1 passed the free radical quenching test at both weight percents.

[0081] The results show that the lipophilically dispersed phenolic polymer particles in the oil phase are ultra-photostable and pass the free radical quenching test. The free radical quenching ability is an indicator of the antioxidant properties of the lipophilic phenolic polymer. The results also show that the lipophilic phenolic polymer particles can be combined with highly photoactive materials to produce ultra-photostable compositions that protect the user from UV-generated free radicals.

[0082] (References) 1. US Patent No. 6,500,411. 2. U.S. Patent No. 6,716,418. 3. US Patent No. 8,309,063. 4. US Patent No. 8,445,562. 5. US Patent No. 8,911,976. 6. US Patent No. 10,035,928. 7. US Patent Application Publication No. 2007 / 0178057. 8. US Patent Application Publication No. 2010 / 0202985. 9. US Patent Application Publication No. 2015 / 0166836. 10. U.S. Patent Application Publication No. 2018 / 0291210. 11. International Patent Application Publication No. WO 2009 / 038477. 12. International Patent Application Publication No. WO 2014 / 144746. 13. International Patent Application Publication No. WO 2014 / 164418. 14. International Patent Application Publication No. WO 2017 / 197530. 15. Pan, X. et al., "Organosolv ethanol ligninfrom hybrid poplar as a radical scavenger: relationship between ligninstructure, extraction conditions, and antioxidant activity", Journal ofAgricultural and Food Chemistry, Vol. 54, pp. 5806-5813 (2006). 16. Cosmetics Europe, "Guidelines for evaluating sun product waterresistance", available online at www.cosmeticseurope.eu / files / 7914 / 6407 / 7400 / Guidelines_for_Evaluating_Sun_Product_Water_Resistance_-_2005.pdf,15 pages (2005). 17. Bleasel, M.D. et al., "In vitro evaluationof sun protection factors of sunscreen agents using a novel UVspectrophotometric technique", International Journal of Cosmetic Science,Vol. 30, Issue 4, pp. 259-270 (2008). 18. The International Lignin Institute, "About lignin", availableonline at www.ili-lignin.com / aboutlignin.php (accessed August 30, 2019).

Claims

1. Phenolic polymer particles; a surfactant on the phenolic polymer particles; Including, Lipophilic phenolic polymer particles, said particles being in a solid state and said phenolic polymer being a water-soluble polymer containing a plurality of OH-substituted phenolic groups.

2. 2. The lipophilic phenolic polymer particle of claim 1, wherein the phenolic polymer particle comprises a material selected from the group consisting of lignin, humates, tannins, plant extracts containing water soluble and / or water dispersible components, and combinations thereof.

3. 3. The lipophilic phenolic polymer particle of claim 1 or 2, wherein the surfactant comprises a material selected from the group consisting of fatty alcohols and polyols; fatty acids; polyglyceryl esters; polyglyceryl polyesters; polyesters having affinity hydroxyl, amine or amide groups; polyurethanes having affinity hydroxyl, amine or amide groups; polyamides having affinity hydroxyl, amine or amide groups; polyacrylates having affinity hydroxyl, amine or amide groups; phosphate esters; polymeric phosphates; phospholipids; ceramides; sphingosines; combinations thereof, copolymers thereof, and crosspolymers thereof.

4. 3. The lipophilic phenolic polymer particle of claim 1 or 2, wherein the surfactant comprises a sphingosine.

5. 3. The lipophilic phenolic polymer particle of claim 1 or 2, wherein the surfactant comprises lecithin.

6. The lipophilic phenolic polymer particles according to claim 1 or 2, wherein the phenolic polymer particles have a particle size of 0.001 to 10.0 microns (μm).

7. the phenolic polymer particles are present in an amount of 0.1 to 75.0 wt. %, and 3. The lipophilic phenolic polymer particle according to claim 1 or 2, wherein the surfactant is present in an amount of from 1.0 to 100.0% by weight of the phenolic polymer particle.

8. 3. The lipophilic phenolic polymer particles according to claim 1 or 2, wherein the dispersion is highly water resistant.

9. 3. The lipophilic phenolic polymer particles according to claim 1 or 2, wherein the dispersion is ultra-light stable.

10. 3. The lipophilic phenolic polymer particles of claim 1 or 2, wherein the dispersion passes the free radical quench test.

11. The lipophilic phenolic polymer particles according to claim 1 or 2, UV protection agent A sunscreen composition comprising:

12. UV protection agents include zinc oxide (ZnO) and titanium dioxide (TiO 2 12. The sunscreen composition of claim 11, wherein said compound is selected from the group consisting of:

13. 3. The lipophilic phenolic polymer particles according to claim 1 or 2 for use in treating or preventing oxidative damage to the skin, said treating or preventing comprising applying said lipophilic phenolic polymer particles to said skin.

14. 3. Lipophilic phenolic polymer particles according to claim 1 or 2 for use in protecting keratinous materials, said protecting comprising applying said lipophilic phenolic polymer particles to said keratinous materials, Lipophilic phenolic polymer particles for said use, wherein said keratinous material is selected from the group consisting of hair, fingernails, toenails and the outer layer of the skin.

15. 3. Lipophilic phenolic polymer particles according to claim 1 or 2 for use in protecting human skin, said protecting comprising applying said lipophilic phenolic polymer particles to said human skin.

16. 3. A lipophilic phenolic polymer particle according to claim 1 or 2 for use in inhibiting lipid peroxidation in the skin, said inhibiting comprising applying said lipophilic phenolic polymer particle to said skin.

17. 3. Lipophilic phenolic polymer particles according to claim 1 or 2 for use in preventing or reducing the appearance of wrinkles and lines on the skin, said preventing or reducing comprising applying said lipophilic phenolic polymer particles to the skin.

18. 3. Lipophilic phenolic polymer particles according to claim 1 or 2 for use in preventing loss of skin elasticity, said preventing comprising applying said lipophilic phenolic polymer particles to said skin.

19. 3. Lipophilic phenolic polymer particles according to claim 1 or 2 for use in preventing thinning of the skin, said preventing comprising applying said lipophilic phenolic polymer particles to the skin.

20. 3. Lipophilic phenolic polymer particles according to claim 1 or 2 for use in preventing pigment darkening of the skin, said preventing comprising applying said lipophilic phenolic polymer particles to the skin.

21. 3. The lipophilic phenolic polymer particles according to claim 1 or 2 for use in attenuating HEV radiation exposure to the skin, said attenuating comprising applying said lipophilic phenolic polymer particles to said skin.

22. 3. Lipophilic phenolic polymer particles according to claim 1 or 2 for use in quenching free radicals in keratinous materials, said quenching comprising applying said lipophilic phenolic polymer particles to said keratinous materials, Lipophilic phenolic polymer particles for said use, wherein said keratinous material comprises hair or skin.

Citation Information

Patent Citations

  • Multifunctional particulate additive for personal care and cosmetic compositions and method of making same

    JP2004522751A

  • Household cleaning and / or laundry detergent compositions containing lignin derivatives

    JP2005522529A

  • Resin material for electric wire / cable or connector

    JP2010116465A

  • Manufacturing method of silica particles and silica particles

    JP2017095297A

  • Multifunctional particulate additive for personal care and cosmetic compositions, and the process of making the same

    US20020182155A1